2019
DOI: 10.1111/jir.12704
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of social support: comparisons between fathers of children with autism spectrum disorder and fathers of children without developmental disabilities

Abstract: Background Research highlights the need for ongoing social support of mothers of children with Autism spectrum disorders (ASD). Despite recognised differences between mothers and fathers, little is known about the particular social support needs of fathers of children with ASD. Broadly, this study aimed to explore the support needs of fathers of children with ASD compared with fathers of children without a disability (W/OD) and the relation between social support, psychological distress and sociodemographic fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…Fathers identified the need for increased professional, public and cultural awareness and education regarding ASD and the need to improve service provision and access (Burrell et al, 2017;Cheuk & Lashewicz, 2016;Manor-Binyamini, 2019). The specific needs of fathers require to be recognised and their needs fully reflected within government education, health and social care policies, thereby seeking to improve the social support provided to fathers and their families (Seymour et al, 2020) Following on from this, is the opportunity for nursing-specific policies to fully reflect the needs of fathers. For example, health visiting, public health nursing, child health nursing and mental health nursing policies need to make explicit their commitment to ensuring that fathers are fully involved in the assessment and diagnostic process.…”
Section: Implications For Nursing Policymentioning
confidence: 99%
See 1 more Smart Citation
“…Fathers identified the need for increased professional, public and cultural awareness and education regarding ASD and the need to improve service provision and access (Burrell et al, 2017;Cheuk & Lashewicz, 2016;Manor-Binyamini, 2019). The specific needs of fathers require to be recognised and their needs fully reflected within government education, health and social care policies, thereby seeking to improve the social support provided to fathers and their families (Seymour et al, 2020) Following on from this, is the opportunity for nursing-specific policies to fully reflect the needs of fathers. For example, health visiting, public health nursing, child health nursing and mental health nursing policies need to make explicit their commitment to ensuring that fathers are fully involved in the assessment and diagnostic process.…”
Section: Implications For Nursing Policymentioning
confidence: 99%
“…A knowledgeable, skilled and confident nursing workforce that is responsive to the concerns of fathers of people with ASD is required to ensure that their needs are sensitively and comprehensively addressed (Dunlap & Filipek, 2020;Ward et al, 2016). There is also an opportunity to involve fathers in multiagency continuing professional development programmes for nurses, healthcare professionals and other specialists in ASD services that develops and improves their knowledge and understanding of the distinct needs of fathers and their specific ongoing social support requirements following diagnosis (Seymour et al, 2020).…”
Section: Implications For Nursing Educationmentioning
confidence: 99%
“…research on fathers is needed, as previous studies have demonstrated some differences between mothers and fathers in interpersonal emotion regulation use and in perceived social support perceptions, especially in the ASD context (Liu et al, 2021;Lloyd et al, 2019;Seymour et al, 2020).…”
Section: Declaration Of Conflicting Interestsmentioning
confidence: 99%
“…The other secondary data analysis appears in Perceptions of social support: Comparisons between fathers of children with ASD and fathers of children without developmental disabilities by Seymour et al . (2020), focused uniquely on the social support of fathers. This paper utilised data from the Longitudinal Study of Australian Children, when the children were 8 to 9 years old.…”
Section: Guide To Papers In This Special Issuementioning
confidence: 99%